STUDI KELAYAKAN USAHA RUMAH POTONG HEWAN TERNAK DAN UNGGAS PADA ASPEK PEMASARAN - Masroatul Fitriyah; Mochamad Reza Adiyanto (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
This study aims to determine how the marketing aspects of slaughterhouses based on the amount of livestock and poultry meat consumption on the island of Madura. This research uses a quantitative approach using demand projections to measure products using import data and supply projections used include trend analysis used to project future sales based on previous data and regression analysis used to determine how many people consume livestock and poultry meat. The variables analyzed in feasibility are demand, supply, and the amount of meat consumption per capita. This study uses secondary data obtained by researchers from the Livestock Service Office and the Central Bureau of Statistics. The results showed that by using the trend analysis method, the production in 2023 according to the type of livestock meat was 26 thousand tons and poultry meat was 768 laying hens. Animal consumption on the island of Madura is very low based on correlation analysis of beef 0.165 per capita and layer meat 0.292 this percentage shows a low significance.